A critical analysis of the international direct tax solutions for businesses in the digital economy - Peres, Monique Helena Alfonso (My University, 2019)
Taxes are not paid where value is created when it comes to the digital economy. Current international tax laws were written before the digital economy started. The digital economy has changed our lives and how business is done. Value is created in different ways by digital businesses compared to traditional businesses. Digital businesses can do business in any jurisdiction in the world without a physical presence. The permanent establishment concept is still based on physical presence which is irrelevant to digital businesses. The permanent establishment concept and its irrelevance to the digital economy will be discussed in the report. Foreign digital businesses use the physical presence required by the permanent establishment concept in their tax planning to reduce their tax liability. The questions that will be answered in the report are how and where value is created and where should digital businesses pay direct taxes such as income tax, amongst other taxes. The purpose of this report is to critically analyse how digital businesses should be directly taxed when they have a significant digital presence with little or no physical presence in a jurisdiction. The report will critically analyse the direct tax solutions that have been proposed to tax businesses in the digital economy.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2019.
Keywords: UCTD; Digital economy; Permanent establishment; Digital economy; Taxation; Electronic commerce; SDG-8: Decent work and economic growth